THE GREAT JOURNALISTIC WALL IN CHINA: PREEMPTIVE BOUNDARY WORK IN THE AGE OF GENERATIVE AI - Kuai, Joanne Xiaoqiong (AoIR Selected Papers of Internet Research, 2026)
This study explores how Chinese journalists perceive, use, and report on artificial intelligence (AI) technologies and the reflected journalist roles. Through qualitative analysis of 18 in-depth interviews with Chinese journalists from various news organizations, the study examines how journalists, as both users and mediators of algorithms, shape public understanding while influenced by the sociotechnical and algorithmic imaginaries (Bucher, 2017; Jasanoff, 2015) surrounding AI. The findings reveal that despite concerns over the opaque knowledge apparatus underpinning the AI value construction, Chinese journalists strive to maintain critical reporting without contributing to media hype. Engaging with the literature on the boundaries and boundary work of journalism (Carlson & Lewis, 2015, 2019), the study argues that Chinese journalists deploy preemptive boundary work to define their profession, as well as safeguard journalistic autonomy (Örnebring & Karlsson, 2022), involving dismissing the potential benefits of GenAI tools, building AI anchors that are less ‘real’ so that people could easily identify the use of AI tools that justifies the investments in journalistic innovation, and insisting on human being the final gatekeepers. Positioned within China’s unique political and media landscape, the research underscores the complexities of journalistic practice in the AI era.